2021
DOI: 10.1101/2021.05.06.442990
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

NERD-seq: A novel approach of Nanopore direct RNA sequencing that expands representation of non-coding RNAs

Abstract: The new next-generation sequencing platforms by Oxford Nanopore Technologies for direct RNA sequencing (direct RNA-seq) allow for an in-depth and comprehensive study of the epitranscriptome by enabling direct base calling of RNA modifications. Non-coding RNAs constitute the most frequently documented targets for RNA modifications. However, the current standard direct RNA-seq approach is unable to detect many of these RNAs. Here we present NERD-seq, a sequencing approach which enables the detection of multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…Nanopore DRS is a well-established long-read sequencing technology to study RNA molecules, typically polyadenylated mRNAs [93][94][95][96][97] . Although several works have shown that this technology can also be used to study short RNA molecules, such as snoRNAs and snR-NAs 96,98 , DRS is inefficient at capturing RNA molecules shorter than 200 nucleotides (nt) and is generally considered unable to capture sequences shorter than ~100 nt 96,97 , limiting its applicability to study short RNA populations, such as tRNAs.…”
Section: Standard Nanopore Drs Results In Low Trna Sequencing Yieldsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanopore DRS is a well-established long-read sequencing technology to study RNA molecules, typically polyadenylated mRNAs [93][94][95][96][97] . Although several works have shown that this technology can also be used to study short RNA molecules, such as snoRNAs and snR-NAs 96,98 , DRS is inefficient at capturing RNA molecules shorter than 200 nucleotides (nt) and is generally considered unable to capture sequences shorter than ~100 nt 96,97 , limiting its applicability to study short RNA populations, such as tRNAs.…”
Section: Standard Nanopore Drs Results In Low Trna Sequencing Yieldsmentioning
confidence: 99%
“…Nanopore DRS is a well-established long-read sequencing technology to study RNA molecules, typically polyadenylated mRNAs [93][94][95][96][97] . Although several works have shown that this technology can also be used to study short RNA molecules, such as snoRNAs and snR-NAs 96,98 , DRS is inefficient at capturing RNA molecules shorter than 200 nucleotides (nt) and is generally considered unable to capture sequences shorter than ~100 nt 96,97 , limiting its applicability to study short RNA populations, such as tRNAs. In addition, the first ~15 nt at the 5′ end of RNA molecules are typically lost in DRS runs 93,99 , as this portion cannot be adequately basecalled due to the increase in the RNA translocation speed when the 5′ end of the molecule exits the helicase 99 .…”
Section: Standard Nanopore Drs Results In Low Trna Sequencing Yieldsmentioning
confidence: 99%